Role of Self-help Groups in Promoting Inclusion and Rights of Persons with Disabilities - K P Kumaran (Disability, CBR and Inclusive Development)
Purpose:This study examined the role of self help groups in addressing some of the problems faced by persons with disabilities such as social exclusion, discrimination, lack of awareness about their rights and privileges, and absence of livelihood programmes. Method: One hundred persons with disabilities were randomly drawn for the study from 50 self help groups in 2 districts that were covered under a popular poverty alleviation programme implemented by the state of Andhra Pradesh  in India.  An interview schedule was used to collect information. Results: Before joining the group, some of the persons with disabilities were mostly confined to their houses, and viewed as less productive and incapable of leading a ‘normal’ life. After joining the groups, they came out of their seclusion and started to work together for their collective welfare and development. They gained knowledge about their rights and privileges and started income generation activities with the help of loans made available to them.  They gained better acceptance within their families, but attitudes of their communities was slower to change. A feeling that “disability is not inability” seemed to have been internalized among the members of the groups. Conclusion: Self-help groups can be very effective in helping persons with disabilities to come out of their isolation and in promoting their participation and inclusion in societal mainstream. Key Words: Self-help group, persons with disabilities doi 10.5463/DCID.v22i2.78